Economics of Sustainable Development and the Bioeconomy. (16th February 2018) - Zilberman, David; Gordon, Ben; Hochman, Gal; Wesseler, Justus
Abstract: Sustainable development can be attained by policies that are derived by analyses that integrate biophysical considerations into economic models. We show that policies and incentives that correct market failure can attain sustainable development through enhancing conservation, recycling, the use of renewable resources, and development of the bioeconomy, which relies on biological processes and feedstock to produce renewable products. The design of sustainable development policies and analysis of the bioeconomy pose new challenges to applied economists, who are uniquely qualified to integrate economic analysis with biophysical considerations.